Allopolyploid origins of the Galeopsis tetraploids--revisiting Müntzing's classical textbook example using molecular tools - Bendiksby, Mika; Tribsch, Andreas; Borgen, Liv; Trávníček, Pavel; Brysting, Anne K (The New phytologist, 2011)
Whole-genome duplication coupled with hybridization is of prime importance in plant evolution. Here we reinvestigate Müntzing's classical example of allopolyploid speciation; the first report of experimental synthesis of a naturally occurring allopolyploid species, Galeopsis tetrahit. Various molecular markers (cpDNA, NRPA2, amplified fragment length polymorphisms (AFLPs)) and flow cytometry were surveyed in population samples of subgenus Galeopsis, including two allopolyploid species and their potential diploid parents. The presence of two divergent copies of single-copy NRPA2 confirms the allopolyploid origins of G. tetrahit and Galeopsis bifida. However, the two allopolyploids do not share the same maternal genome, as originally suggested by Müntzing. The results support independent origins, but not recurrent formation, of the two allotetraploids. Data further indicate frequent gene flow and introgression within ploidy levels, but less so between ploidy levels. Our results confirm and elaborate on Müntzing's classical conclusion about allopolyploid origins of G. tetrahit and G. bifida. We address questions of general interest within polyploidy research, such as recurrent formation, gene flow and introgression within and between ploidy levels.
Keywords: DNA, Chloroplast; chloroplasty; DNA, Plant; Cell Nucleus; Phylogeny; Sequence Analysis, DNA; genetické markery; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; buněčné jádro; sekvenční analýza DNA; Amplified Fragment Length Polymorphism Analysis; rostlinné geny; Genes, Plant; Flow Cytometry; fylogeneze; Genetic Markers; Bayesova věta; DNA rostlinná; Chloroplasts; Lamiaceae; DNA chloroplastová; průtoková cytometrie; hluchavkovité; polyploidie; Polyploidy; Bayes Theorem